2011
DOI: 10.1089/gtmb.2010.0265
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1 Alpha C1772T Gene Polymorphism and Glioma Risk: A Hospital-Based Case–Control Study from China

Abstract: This study suggested that CT genotype and the T allele of HIF-1α C1772T gene polymorphism were associated with a higher glioma risk in the Han population of China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
7
1
Order By: Relevance
“…An association of CT genotype of g.C1772T polymorphism has been reported with large tumor size in esophageal squamous cell carcinoma (Ling et al, 2005) and with more severe ulcerative growth pattern in colorectal adenocarcinoma (Fransen et al, 2006). In contrast to our findings, higher frequency of CT genotype has been reported in patients with breast (Naidu et al, 2009), prostate (Chau et al, 2005;Foley et al, 2009), pancreatic cancer and glioma (Xu et al, 2011). For g.C1772T polymorphism, we did not observe any significant differences in genotype and allele distribution between breast cancer patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…An association of CT genotype of g.C1772T polymorphism has been reported with large tumor size in esophageal squamous cell carcinoma (Ling et al, 2005) and with more severe ulcerative growth pattern in colorectal adenocarcinoma (Fransen et al, 2006). In contrast to our findings, higher frequency of CT genotype has been reported in patients with breast (Naidu et al, 2009), prostate (Chau et al, 2005;Foley et al, 2009), pancreatic cancer and glioma (Xu et al, 2011). For g.C1772T polymorphism, we did not observe any significant differences in genotype and allele distribution between breast cancer patients and controls.…”
Section: Discussioncontrasting
confidence: 99%
“…Another case-control study showed that XRCC1 Arg399Gln polymorphism is a significant risk factor and that the 399Gln (G) allele carries a 3.5 times greater risk for glioma, whereas the PARP1 Val/Ala genotype may be protective against it (Yosunkaya et al, 2010). A hospital-based case-control study suggested that CT genotype and the T allele of hypoxiainducible factor-1a C1772T gene polymorphism were associated with a higher glioma risk in the Han population of China (Xu et al, 2011). From a total of 11 SNPs in 7 cytokine genes within a hospital-based study, Brenner et al (2007) found that the IL4 (rs2243248, -1098T > G) and IL6 (rs1800795, -174G > C) polymorphisms were significantly associated with risk for glioma in the pooled analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Among 16 HIF1A SNPs associated with 40 different phenotypes six SNPs have been associated with increased risk for 14 cancer types: rs113182457, rs11549465, rs11549467, rs199775054, rs2057482, and rs2301113 . These six SNPs were most frequently associated with breast, lung, colorectal (CRC), gastric, prostate, oral cancer, and renal cell carcinoma (RCC).…”
Section: Hif1a and Cancer Riskmentioning
confidence: 99%
“…Among 16 HIF1A SNPs associated with 40 different phenotypes six SNPs have been associated with increased risk for 14 cancer types: rs113182457, 45 rs11549465, [20][21][22]24,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58]68,112 rs11549467, 35,36,41,43,44,50,[55][56][57][58]70,75,76,78,81,88,104,105 rs199775054, 108 rs2057482, 32,79,110,…”
Section: H I F 1 a A N D Ca N C E R R I S Kmentioning
confidence: 99%